2008
DOI: 10.1172/jci36130
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine network in asthma and chronic obstructive pulmonary disease

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) are very common inflammatory diseases of the airways. They both cause airway narrowing and are increasing in incidence throughout the world, imposing enormous burdens on health care. Cytokines play a key role in orchestrating the chronic inflammation and structural changes of the respiratory tract in both asthma and COPD and have become important targets for the development of new therapeutic strategies in these diseases. IntroductionThe most common infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
730
2
35

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 839 publications
(783 citation statements)
references
References 129 publications
(129 reference statements)
16
730
2
35
Order By: Relevance
“…IL-8 is a potent neutrophil chemoattractant and activator of neutrophils and is produced by a number of airway inflammatory cells, including neutrophils (18). Besides, IL-6 plays important role in asthma, especially in neutrophil infiltration (19). VEGF, previously known as vascular permeability factor, is the most specific growth factor for vascular endothelium (20).…”
Section: Il-31 In Children With Allergic Rhinitismentioning
confidence: 99%
“…IL-8 is a potent neutrophil chemoattractant and activator of neutrophils and is produced by a number of airway inflammatory cells, including neutrophils (18). Besides, IL-6 plays important role in asthma, especially in neutrophil infiltration (19). VEGF, previously known as vascular permeability factor, is the most specific growth factor for vascular endothelium (20).…”
Section: Il-31 In Children With Allergic Rhinitismentioning
confidence: 99%
“…7,8 The actions of cytokines in the lung are widely investigated because of the interface of the airway with the environment, the susceptibility of the lung to infection, and the burden of chronic inflammatory airway diseases, particularly asthma and chronic obstructive pulmonary disease (COPD). 9,10 As an experimental model, the lung is ideal for the study of inflammatory responses due to the ease of direct delivery of cytokines to the airway in vivo and the ability to assay cultured primary airway epithelial cells in vitro. Using approaches similar to these, our group has recently demonstrated that airway epithelial cell IL33 (interleukin 33) leads to IL13 production and lung pathology in a mouse model and in cells obtained from patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…The major cause of COPD is cigarette smoking, although other environmental pollutants may also serve as triggers in susceptible individuals. These insults induce chronic inflammation and remodeling, including structural changes and destruction of alveolar tissue, within the lung [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The key effector cells within the airway tissue of COPD patients include macrophages, CD8+ T lymphocytes and neutrophils, releasing toxic mediators [2,5]. The destruction of alveolar tissue (emphysema) is thought to be caused by the release of proteinase (such as matrix metalloproteinase from alveolar macrophages) or as a consequence of an autoimmune response (e.g.…”
Section: Introductionmentioning
confidence: 99%